Blood–brain barrier breakdown in septic encephalopathy and brain tumours* - Davies, DC (Blackwell Science Inc, 2002)
Septic encephalopathy is associated with breakdown of the blood–brain barrier and cerebral oedema. These features are also common properties of brain tumours. Perimicrovessel oedema, disruption of associated astrocyte end feet and neuronal injury occur in a porcine model of acute septic encephalopathy. The adrenergic system has been implicated in the inflammatory response to sepsis and may play a role in controlling blood–brain barrier permeability, since the β(2)-adrenoceptor agonist dopexamine inhibits perimicrovessel oedema formation whereas the α(1)-adrenoceptor agonist methoxamine provokes it. Electron microscopy revealed tight junction opening in high-grade astrocytoma microvessels. Expression of the tight junction protein occludin is reduced in these microvessels and this reduction is inversely correlated with the degree of cerebral oedema. Normal astrocytes secrete factors that induce barrier properties in endothelial cells, whereas high-grade astrocytomas secrete vascular endothelial growth factor, which stimulates angiogenesis, down regulates occludin and increases endothelial cell permeability. The water channel protein aquaporin-4 is normally expressed in astrocyte foot processes around cerebral microvessels. Its expression is massively up-regulated in high-grade astrocytoma and around metastatic adenocarcinoma. There is a significant correlation between aquaporin-4 expression and the degree of cerebral oedema, but it is not clear whether increased aquaporin-4 expression enhances oedema formation or clearance. These results suggest that the pathophysiology of brain oedema is multifactorial, but that there may be common processes operating regardless of the aetiology.